The Under-Registration of Births in Latin America - Suzanne Duryea; Analía Olgiati; Leslie Stone (Inter-American Development Bank, Research Department, 2006)
Approximately 14 percent of births are unregistered in Latin America according to estimates by UNICEF (2001). Children who lack an official birth certificate can be denied access to social services, including enrolling in school and accessing health services. This paper examines the under-registration of births in six Latin American countries (Bolivia, Brazil, Colombia, the Dominican Republic, Peru, and Nicaragua) using Demographic and Health Surveys (DHS). Under-registration of children younger than 5 is found to range from 8. 4 percent in Peru to 25. 8 percent in the Dominican Republic. Striking regional differences are found in all six countries. – – En América Latina se deja de inscribir en el registro civil aproximadamente 14% de los nacimientos, según un cálculo de la UNICEF (2001). A los ni\~nos que carecen de un documento donde conste su nacimiento se les puede negar el acceso a servicios sociales, incluida la matriculación en la escuela y el acceso a servicios médicos. En este trabajo se analiza la falta de registro de nacimientos en seis países latinoamericanos `Bolivia, Brasil, Colombia, República Dominicana, Perú y Nicaragua` empleando encuestas demográficas y de servicios de salud (DHS, por sus siglas en inglés). Se halló que la falta de inscripción de ni\~nos de menos de cinco a\~nos va de 8,4% en Perú a 25,8% en República Dominicana. En los seis países se hallaron diferencias regionales muy considerables. Baje el Archivo PDF
Keywords: 330; Kommunalverwaltung; Lateinamerika; Fertilität